1990
DOI: 10.1111/j.1745-6584.1990.tb02266.x
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Microbial Populations in Buried‐Valley Aquifer Sediments from Northeastern Kansas

Abstract: Twenty‐two aseptically collected sediment core samples were obtained from below the water table (60 to 280 feet deep) at four pristine sites along a major buried‐valley aquifer system in northeastern Kansas. Samples were examined for total numbers of bacteria, viable aerobic bacteria, protozoa, and fungi. Contiguous samples were obtained in some transition zones of sediment texture or color in order to detect possible population shifts over small vertical distances related to changes in sediment characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 29 publications
3
32
0
Order By: Relevance
“…There is often no significant difference between the unsaturated and saturated zone, only a slight decrease with depth. Higher numbers were usually found in coarse grained, highly permeable layers, while there was not always a clear correlation between OC and cell number (Balkwill and Ghiorse 1985;Bone and Balkwill 1988;Konopka and Turco 1991;Sinclair et al 1990). In groundwater from different types of aquifers, planktonic cell numbers often range between 10 4 and 10 6 cells mL −1 , about two orders of magnitude lower than the number of benthic cells.…”
Section: Bacterial Abundance and Activity In Aquifersmentioning
confidence: 99%
See 1 more Smart Citation
“…There is often no significant difference between the unsaturated and saturated zone, only a slight decrease with depth. Higher numbers were usually found in coarse grained, highly permeable layers, while there was not always a clear correlation between OC and cell number (Balkwill and Ghiorse 1985;Bone and Balkwill 1988;Konopka and Turco 1991;Sinclair et al 1990). In groundwater from different types of aquifers, planktonic cell numbers often range between 10 4 and 10 6 cells mL −1 , about two orders of magnitude lower than the number of benthic cells.…”
Section: Bacterial Abundance and Activity In Aquifersmentioning
confidence: 99%
“…cyclic adenosine monophosphate (cAMP)) in order to increase the cultivation efficiency for heterotrophic bacteria from aquatic (marine) environments (Bruns et al 2002). In some cases, however, the number of culturable counts was nearly equal to the number of direct visual counts, indicating that most cells were in an active state (Sinclair et al 1990). …”
Section: Bacterial Abundance and Activity In Aquifersmentioning
confidence: 99%
“…The ratio of active bacteria (CFU/AODC) ( Table 2) as well as the viable counts and the total number of bacteria (Fig. 2) are within the range of values reported from subsurface sediments [3,7,33,36]. The very small percentage of active bacteria indicates that a large part of the total amount of bacteria was inactive or unculturable, especially in the two glacial clay samples (20.4 and 27.5 robs).…”
Section: Microbial Investigationsmentioning
confidence: 63%
“…Other investigators have also found the highest total number of bacteria (AODC) in samples with a high content of clay and silt [7] and in the clay and silt fraction of size-fractionated sediment [16]. In contrast, measurements of microbial population density (AODC, viable count) have shown positive correlations with sand content and moderate negative correlations with clay content in other subsurface systems [10,32,33]. We, Chapelle et al [7], and Harvey et al [16] enumerated bacteria on a filter, whereas the other investigators embedded the sediment sample in an agar smear.…”
Section: The Influence Of Abiotic Parametersmentioning
confidence: 99%
See 1 more Smart Citation